Infection Control in Acute Care Facilities: Evidence-Based Patient Safety - Lindsay E Nicolle (Canadian Journal of Infectious Diseases)
Infection control in acute care facilities has a noble history. These programs were born of the nosocomial penicillin-resistant Staphylococcus aureus outbreaks in the post-World War II era. Over the past four decades, an impressive body of evidence has emerged that documents the effectiveness of infection control programs and systematically evaluates specific program components. Fumigation, tacky floor mats, shoe covers and 'reverse' isolation have disappeared. They are replaced by focused surveillance programs, prophylactic antimicrobial therapy, outbreak investigation and control, routine barrier practices and molecular typing of organisms for epidemiological analysis.